Development of Augmented Reality-Based Learning Media on Hindu Temples: Pengembangan Media Pembelajaran Candi Hindu Berbasis Augmented Reality - Wardani, Kurnia; Widodo, Tri (Universitas Sam Ratulangi, 2025)
Abstract — This study addresses the low level of student interest and understanding in history lessons, particularly on the topic of Hindu temples, which is commonly taught through conventional methods such as lectures and textbooks. Interactive media is considered a promising alternative to enhance engagement and provide a more immersive learning experience. This research aims to develop Augmented Reality (AR)-based learning media to support junior high school (SMP) students in understanding historical material related to Hindu temples. The development process followed the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The AR application was created using Unity and the Vuforia Software Development Kit (SDK). The final product—a mobile AR learning application—was tested on Grade VII students at SMP Taman Dewasa Jetis, Yogyakarta. Validation results indicate high feasibility, with media experts rating the application at 97%, material experts at 95.5%, and student responses reaching 89%, all categorised as “very feasible.” Effectiveness testing revealed a significant improvement in student understanding, with an N-Gain score of 62%, placing it in the “moderately effective” category. These findings suggest that AR-based learning media are both feasible and effective in enhancing student interest and comprehension of historical content. The application represents an innovative alternative for creating a more interactive, engaging, and meaningful learning experience in the classroom. Key words — Learning Media, Augmented Reality (AR), History of Hindu Temples, Effectiveness Abstrak — Latar belakang dari penelitian ini adalah rendahnya minat dan pemahaman siswa terhadap pelajaran sejarah, terutama pada topik candi Hindu, yang selama ini disampaikan melalui metode konvensional seperti ceramah atau buku teks. Media interaktif dinilai mampu memberikan pengalaman belajar yang lebih menarik dan mendalam. Penelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis teknologi Augmented Reality (AR) sebagai sarana bantu dalam memahami materi sejarah tentang candi-candi Hindu bagi siswa Sekolah Menengah Pertama (SMP). Pengembangan media dilakukan dengan menggunakan model ADDIE (Analysis, Design, Development, Implementation, dan Evaluation), serta memanfaatkan perangkat lunak Unity dan Vuforia SDK. Produk akhir berupa aplikasi pembelajaran AR diuji coba kepada siswa kelas VII di SMP Taman Dewasa Jetis Yogyakarta. Hasil validasi menunjukkan bahwa aplikasi ini sangat layak digunakan, dengan penilaian ahli media sebesar 97%, ahli materi sebesar 95,5%, dan tanggapan siswa sebesar 89%. Sementara itu, hasil uji efektivitas menunjukkan peningkatan pemahaman siswa dengan skor N-Gain sebesar 62%, yang termasuk dalam kategori cukup efektif. Dari hasil tersebut dapat disimpulkan bahwa media pembelajaran berbasis Augmented Reality ini tidak hanya layak digunakan, tetapi juga efektif dalam meningkatkan minat dan pemahaman siswa terhadap sejarah candi Hindu. Media ini menjadi alternatif inovatif dalam menciptakan pengalaman belajar yang lebih interaktif, menarik, dan bermakna di kelas. Kata kunci — Media Pembelajaran, Augmented Reality, Sejarah Candi Hindu, Efektivitas.